VD_FINDINFO HC / 2016 / 266 vom 11. Februar 2016 - VD Tribunal cantonal (2016)
MASSE EN FAILLITE, CAISSE DE COMPENSATION{AVS/AI}, ACTION EN RÉVOCATION, COTISATION AVS/AI/APG | 288 LP, 157 CPC (CH), 55 CPC (CH)